2018
DOI: 10.1186/s13287-018-0976-0
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA CDR1as regulates osteoblastic differentiation of periodontal ligament stem cells via the miR-7/GDF5/SMAD and p38 MAPK signaling pathway

Abstract: BackgroundPeriodontal ligament stem cells (PDLSCs) are considered as candidate cells for the regeneration of periodontal and alveolar bone tissues. Antisense to the cerebellar degeneration-related protein 1 transcript (CDR1as), which is a newly discovered circular RNA (circRNA), has been reported to act as an miR-7 sponge and to be involved in many biological processes. Here, we investigated the potential roles of CDR1as and miR-7 in the osteogenic differentiation of PDLSCs.MethodsThe expression pattern of CDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
190
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(194 citation statements)
references
References 49 publications
4
190
0
Order By: Relevance
“…It was showed that OSCC tissues have abundant circRNAs, and multiple circRNAs significantly differentially expressed. It was reported that hsa_circ_0008309 and hsa_circ_001242 was significantly downregulated in OSCC tissues, correlated with pathological differentiation of OSCC, and may act as a potential novel biomarker for the diagnosis and treatment of OSCC . In addition, salivary hsa_circ_0001874 and hsa_circ_0001971 also act as biomarkers for diagnosing OSCC .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was showed that OSCC tissues have abundant circRNAs, and multiple circRNAs significantly differentially expressed. It was reported that hsa_circ_0008309 and hsa_circ_001242 was significantly downregulated in OSCC tissues, correlated with pathological differentiation of OSCC, and may act as a potential novel biomarker for the diagnosis and treatment of OSCC . In addition, salivary hsa_circ_0001874 and hsa_circ_0001971 also act as biomarkers for diagnosing OSCC .…”
Section: Discussionmentioning
confidence: 99%
“…miR‐182‐5p promoted tumor growth of OSCC through inhibition of CAMK2N1 . miR‐218‐5p was downregulated in OSCC and it promoted invasion of oral squamous cell carcinoma cells by activating CD44‐ROCK . Although miRNAs have been extensively studied in OSCC, there are still a large number of unknown miRNAs needed further study to discover the unknown functions and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mm9_circ_009056 could act as a sponge of miR‐22‐3p, regulating the expression of BMP7 to promote bone formation . CircRNA CDR1as could down‐regulate miR‐7 to activate p38 MAPK pathway, which enhanced the osteogenesis of periodontal ligament stem cells . However, the roles of circRNAs in recombinant NELL‐1‐induced osteogenesis of hASCs remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA BANP and circRNA ITCH can interact with miRNA34a and miRNA146a to regulate osteogenic differentiation of the periodontal ligament stem cells via the MAPK pathway . Promotion of osteogenic differentiation of the periodontal ligament stem cells related to circRNA CDR1as is modulated through the Smad‐dependent and p38 MAPK signaling pathways …”
Section: Discussionmentioning
confidence: 99%